An experimental study on storing thermal energy in packed beds with saturated steam as heat transfer fluid. (15th November 2017) - Edwards, Jacob; Bindra, Hitesh
Highlights: Experimental results are obtained with steam injection in Packed bed TES. Steam flow rate strongly affects the axial thermal dispersion in packed beds. Fractional heat losses are much higher with air as HTF in comparison to steam. Abstract: Large number of solar thermal power plants operating or being designed use steam as a working fluid or heat transfer fluid. Therefore, a thermal energy storage (TES) system which can directly store the energy from steam can improve the demand-supply mismatch of thermal or electrical energy. Packed bed TES systems with solid rocks as packing material are one of the most economical and robust energy storage solutions available. This study investigates thermal energy storage process in packed bed systems with steam as heat transfer fluid (HTF). Experiments were conducted to understand thermal response of cylindrical packed bed filled with uniform and chemically inert alumina particles upon saturated steam injection along the axial direction. Axial thermal gradients determine the efficiency of the storage process. Saturated steam is introduced at different flow rates leading to different thermal gradients in the axial direction during different stages of thermal storage process. Rate of steam injection significantly impacts the modes of heat transfer– advection and diffusion. These experimental studies were extended with air as a HTF to compare thermal gradients in the bed under extremely different heat injection rates. In case of steam injection, wall heat loss rate is significantly lower than heat injection rate whereas, wall heat loss rate is comparable to heat injection rate in case of hot air injection.